ANALISIS PEMBANGUNAN SALURAN IRIGASI MENGGUNAKAN BETON PRACETAK (Jurnal Spesialis Teknik Sipil (JSpTS), 2021)
Irrigation area of the Banjaranyar reservoir, the current condition of the irrigation network requires proper maintenance of the irrigation network. Based on these problems, it is necessary to study the maintenance of the irrigation canal of the Banjaranyar reservoir. Therefore, a lot of research is needed on how to realize the building with an effective cost and implementation time. In the sense that with minimal funds, it can produce maximum maintenance work with the right allocation.The analysis is carried out using the critical path method, so it is expected that the time and cost allocations can be calculated with certainty in accordance with the availability of work package time allocations in one budget year with smaller costs during the construction service life.The purpose of this thesis is to analyze the cost of irrigation construction using precast concrete using the critical path method and to analyze the timing of irrigation development using precast concrete using the critical path method.The result of this research is the acceleration from 90 calendar days to 60 calendar days can be done by rescheduling by eliminating the lag time between work activities.